Elite boxers` performance control methods in varied training conditions - Korzhenevsky, A. N.; Kurguzov, G. V.; Klendar, V. A.; Mamychkin, O. M. (Theory and Practice of Physical Culture, 2020)
Middle altitude oxygen-deficient trainings are ranked among the most popular physical efficiency and individual resource mobilizing methods. Objective of the study was to analyze effects of benefits of the elite boxers` performance control methods in customizable training conditions. The study found the elite boxers` altitude trainings being of no effect on the oxygen transportation efficiency of the blood circulation system; although the high-intensity endurance trainings were found to improve the aerobic energy supply mechanisms and build up the maximal energy generation capacity. Aerobic-ala?tate altitude trainings combined with the predominantly aerobic-anaerobic traditional trainings were found inefficient for the functionality building purposes, with the athletic performance efficiency limited by the neuromuscular system fatigue and stress on the cardiovascular system. The altitude and traditional trainings of elite boxers need to be designed and managed so as to effectively harmonize the varied-intensity training tools and give a special priority to sub-maximal workloads (with HR of 180+ beats per min) to improve the maximal aerobic and anaerobic capacities. Full rehabilitation days are recommended, particularly after the shock training days and competitions to effectively prevent fatigue and burnouts and improve the all-round and special boxing performance efficiency.